Agropolitan Sea Cucumber Farming in Mapan-Mapan, Pitas Sabah: Big Spending Small Success - James M. Alin; Datu Razali Datu Eranza (Universiti Malaysia Sabah, 2017)
This paper investigated why sea cucumber farming -Agropolitan balat (Holothuria Scabra spp.) Mapan-Mapan in Pitas, Sabah funded by taxpayers’ money was not successful in term of economic returns. Between the first (2013) and third year of this project (2015) the authors visited the site more than 20 times. Primary data particularly on sales were collected by interviewing participants of the project. Details on costing for constructing sea cucumber cages (or enclosure) was provided by the joint venture company. Economic returns from each cage were calculated using Profit Loss analysis. Results are as follows; firstly, the marginal return from two inputs of farming i.e. capital and physical labor was increasing in the beginning of Round 1 but it was diminishing from February, 2014 all the way to the end of Round 1. Secondly, the expected Break Even in round 2 (Year 3) did not materialized due to; (i) incentive to work among participants was severely affected by subsidization and (ii) they were not motivated to put efforts or take any precautionary measures to minimize losses during the annual monsoon months.